Property investment decision in Batam City - Yulfiswandi Yulfiswandi; Elissa Jocelynn; Robin Robin (FORUM EKONOMI, 2022)
The aim of this research is to find out factors affecting property investment decision in Batam. Investment decision is defined as how a person decides on investment to select the right alternative and type of business. The independent variables in this study are accounting information, self-image/firm-image coincidence, neutral information, advocate recommendations, and personal financial need. The object of this study is property investors in Batam. This study distributed 300 questionnaires and selected 250 questionnaires to be processed/analyzed. The results show that accounting information does not significantly affect the investment decision, meanwhile self-image/firm-image coincidence, neutral information, advocate recommendations, and personal financial need significantly affect investment decision in Batam.